Optimum periodic maintenance policy of repairable multi-component system with component reallocation and system overhaul. (March 2022) - Fu, Yuqiang; Wang, Jun
Highlights: Joint optimization of component reallocations and system overhauls for multi-component systems. Multiple times of component reallocations and system overhauls in a life cycle are considered. A decomposition method is proposed. Virtual age is used to model the failure rate of the component. Abstract: Motived by cost savings, this paper studies a new periodic maintenance policy for multi-component systems, for which multiple component reallocations and system overhauls are jointly implemented aperiodically at fixed times and components are minimally repaired immediately after failures in a life cycle. Different workloads or conditions of different positions can lead to different degradation processes of components, thus component reallocation can be used to balance the degradation between components at different positions, which has been widely studied. System overhaul can improve the conditions of components by imperfect or perfect repair. Component reallocation and system overhaul are mutually dependent and jointly affect the degradation of components and the maintenance cost of a system. In this paper, the failure rate functions of components are modeled using virtual age, and then a binary mixed integer nonlinear programming model is established to determine the optimal time and assignment for component reallocations, and the optimal time and degree for system overhauls by minimizing the long-run average maintenance cost of the system. Further, the number of system overhauls is proved to be finite, and a decomposition method is proposed. Numerical examples are provided to show the effectiveness of the joint of component reallocations and system overhauls.